Dimensions of Supermarket Service Quality: A Sri Lankan Perspective. - Sivathaasan, N.; Chanaka, U.; Sivapalan, A. (Asian Journal of Empirical Research, 2014)
The purpose of this study is to develop an instrument, determining dimensions of retail service quality with a specific focus on supermarket industry in Sri Lanka. This was by re-examining the RSQS (Retail Service Quality Scale) model, originally developed by Dabholkar, Thorpe and Rentz (1996) and to put forward a model, suitable to Sri Lankan perspective. The questionnaire was used as a research instrument and a total of 150 usable responses (n = 150) were obtained using Systematic Quasi-Random Sampling. Further, the study employs exploratory factor analysis (EFA) for the purpose of data analysis. The modified RSQS model consists of five dimensions or critical factors as detected by exploratory factor analysis. They are personal interaction, physical aspects, reliability, courtesy and convenience. In addition, factors extracted from the analysis accounted for 59.844 % of the total variability. The findings of this research could be generalized to the countries similar to this category.
Keywords: Retail service quality; exploratory factor analysis; Sri Lanka; supermarket industry